Effects of global and domestic tobacco control policies on cigarette consumption per capita: an evaluation using monthly data in China. Issue 6 (19th June 2019) - Xu, Xiaoxin; Zhang, Xiulan; Hu, Teh Wei; Miller, Leonard S; Xu, Mengnan
Abstract : Introduction: China consumes 44% of the world's cigarettes. Robust tobacco control measures are needed to contain the trend of increasing cigarette consumption. This paper examines the effectiveness of policy interventions introduced in China on reducing the country's tobacco use. Methods: The paper uses data on China's monthly cigarette consumption per capita from January 2000 to June 2017 to estimate the impact of specific policies on China's tobacco consumption. Tobacco consumption is calculated from monthly sales data from the China National Tobacco Corporation and demographic data from the China National Bureau of Statistics. The policies studied include the WHO Framework Convention on Tobacco Control (FCTC), national tobacco-related policy changes and two tobacco tax increases implemented in China during the study period. Segmented regression analysis is used to estimate the immediate effects of the policies studied and changes in the time trends resulted from these policy changes. Findings: The impact of national policy changes in China is almost 20 times greater than the impact of the WHO FCTC treaty itself, and national policy changes in tobacco control are a determining factor in reversing the trend of increasing tobacco consumption in China. The 2015 tax increase, which raised retail cigarette prices, produced both immediate and trend effects, with a total incremental effect 7.8 times that of the 2009 tax increase, which did not result in higher cigarette prices for the consumer. Interpretations: Translating global tobacco control policies into domestic policies will generate a much greater impact on reducing average cigarette consumption, and tobacco taxes that are reflected in the retail prices of cigarettes will be more effective in reducing cigarette consumption.